British Asian Muslim Women, Multiple Spatialities, and Cosmopolitanism: By Fazila Bhimji (New York: Palgrave Macmillan, 2012. 176 pages.) (American Journal of Islam and Society, 2014)
This book is a valuable contribution to the growing body of research on theexperiences and identities of British Muslim women. Intersections betweengender, ethnicity, and Islam only became a prominent theme in British socialsciences when the need for a careful and fair investigation of Muslim women’srealities arose during the last decade due to the unfolding of several Islamorientedpolicy debates (i.e., politicians’ critiques of the niqab) and the introductionof legislation designed to tackle “violent extremism” and “honorcrimes.” The way these matters were represented in the media and policy documentshas recycled and reinforced the age-old Orientalist stereotypes of Muslimwomen as silent and passive victims of patriarchal oppression.The author challenges these stereotypes, which are often expressedthrough depictions of Muslim women as spatially anchored and restricted.Thus this book focuses on cosmopolitan practices, particularly spatial andsocial transitions, among second-generation British Asian Muslim women.This approach brings together Bhimji’s earlier work, in particular articlesdealing with these women’s online interactions focused on religion (2005),travelling to and belonging in South Asia (2008), and religious study circles(2009). The monograph is updated with new themes (e.g., case studies ofprominent artists) and applies the analytic lens (viz., the concepts of spatialitiesand cosmopolitanism) adopted in her article on traveling overseas, toall of the issues discussed.The idea of these women crossing geographical, political, and socialboundaries runs throughout the book in order to identify how the stereotypemay be challenged. Bhimji demonstrates that cosmopolitanism, commonlyunderstood as a rejection of localized identities in favor of global ones andwhich is based on social, cultural, and economic privilege, may also be interpretedas a willingness to cross boundaries and engage with difference. Asboundaries and differences form a range of spaces, Bhimji builds her argumentby utilizing a multi-method approach to her data. Not only does she engagein “traditional” ethnographic research with the women attending mosquebasedstudy groups in northern England, as well as women who travel to SouthAsia and beyond, but she also includes media texts, online discussion transcripts,and case studies (i.e., a comedian, a poet, a visual artist, and a political ...